Model Pemberdayaan Pedagang Perempuan Melalui Pengembangan Usaha Pembuatan Ikan Asap di Kota Palembang - Hikmah Laili; Y Yunindyawati (Jurnal Empirika, 2018)
This thesis entitled "Empowerment Model of Women Traders through Development of Smoke Fish Production in Palembang City". The purpose of this study is to find out how the potentials and opportunities of women smoke fish producers and the constraints faced by women smoke fish producers, and to find out how the model of empowerment of women smoke fish maker in the city of Palembang. This research is a descriptive qualitative research that describes the reality of being studied and done purposively. Informants in this study amounted to thirteen people. Data collection techniques using in-depth interviews, observation, and documentation. Analyzed using the concept of Women In Development (WID) from Moser. The results of this study indicate that smoky fishmakers have potential in themselves such as high self-esteem, discipline in acting, creativity, high sense of responsibility, courage to face all risks, and opportunities that are utilized such as utilizing environmental conditions and the number of requests consumer. as well as obstacles such as capital difficulties, difficulty in obtaining raw materials, marketing difficulties and managing the business. From the results of these potentials and opportunities and obstacles,there emerged an empowerment model for female traders of smoked fish, while the model used is the Pro-poor Capacity Improvement Model (PCIM) model. With this model, it is expected that the female smokers willachieve a prosperity.